Minimalna plača v stališčih Evropskega odbora za socialne pravice in nadzornih teles Mednarodne organizacije dela - Kresal, Barbara (Delavci in delodajalci, 2015)
The contribution addresses one of the most important issues of labour law, i.e. the minimum wage. It is an essential aspect of the concept of decent work and the human rights' approach when dealing with labour relations. The European Social Charter guarantees the right to a remuneration such as to ensure a decent standard of living. The provision of an adequate living wage is explicitly mentioned in the Preamble of the ILO Constitution and a minimum living wage for all employed who are in need of such protection in the Declaration of Philadelphia; ILO conventions on minimum wage are relevant as well. The contribution analyses the interpretations and opinions of the European Committee of Social Rights and of the supervisory bodies of the ILO as regards different (legal) aspects of the minimum wages regulation.
Keywords: človekove pravice; Evropska unija; minimalna plača; plače; pravna ureditev; socialna varnost